Proceedings of SPE/PS-CIM/CHOA International Thermal Operations and Heavy Oil Symposium 2005
DOI: 10.2523/97748-ms
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Emulsion Behaviour of Athabasca Extra-Heavy-Oil Produced by SAGD

Abstract: fax 01-972-952-9435. AbstractThe production of extra heavy oil (or bitumen) through the SAGD method (Steam Assisted Gravity Drainage) requires the generation and injection into the reservoir of a great quantity of steam. A typical value of the steam/oil ratio is around 3, which means that a 100,000 bopd development requires the injection of 300,000 bcwepd (barrels of cold water equivalent per day) of steam, and that a corresponding quantity of hot water will be co-produced with the oil. The production of extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The topic of "emulsification phenomenon" during the typical SAGD process was covered in the literature based on the experiments conducted using scaled physical models as well as field-scale data [24,[26][27][28][29][30][31]. According to the field-scale trials of the SAGD process, the produced liquid is in the emulsion state composed of mobilized oil and water (either stable or unstable depending on the physicochemical characteristics of the interacting liquids as well as process operating conditions).…”
Section: Emulsification Phenomenonmentioning
confidence: 99%
“…The topic of "emulsification phenomenon" during the typical SAGD process was covered in the literature based on the experiments conducted using scaled physical models as well as field-scale data [24,[26][27][28][29][30][31]. According to the field-scale trials of the SAGD process, the produced liquid is in the emulsion state composed of mobilized oil and water (either stable or unstable depending on the physicochemical characteristics of the interacting liquids as well as process operating conditions).…”
Section: Emulsification Phenomenonmentioning
confidence: 99%
“…Applications of DSC for characterizing complex emulsified systems are described in several papers [6,[14][15][16][17][18][19][20][21]. We will present here recent examples related to the case of complex emulsions encountered in the oilfield industry.…”
Section: Applicationsmentioning
confidence: 99%
“…2 shows a typical W/O emulsion produced from SAGD well in Hangingstone, Canada. As evident through some previous experimental studies on this phenomenon [3,6,[8][9][10][11], it has been suggested that W/O emulsions are mostly produced during the SAGD process. Especially, Sasaki et al [8,9] conducted experimental studies of SAGD process by using two-dimensional scaled reservoir model to investigate fluids flow characteristics in the steam chamber.…”
Section: Introduction mentioning
confidence: 84%